Electrochemical machining behaviour of AA6063-TiC composites by using response surface methodology. (2020) - Saravanan, S.; Balan, A.V.; Dinesh, S.; Vijayan, V.
Abstract: In this research work, the production and machining of aluminium metal matrix composites were investigated. AA6603 base metal and TiC as reinforcement at propositions ranging from 0 to 9 wt% are used. The material being proposed for the application in aerospace industries and to obtain critical surface finish levels, electro chemical machining process is adopted. The surface roughness is measured as the response by varying the % of reinforcement, voltage and electrolyte concentration. ANOVA, response surface methodology and regression analysis has been carried to identify the most contributing parameter, optimal combination and prediction of deviation from experimental values.